Wojna oczami „nacbola”. Obraz wojny w zbiorze opowiadań Smrt Eduarda Limonowa - Kołakowski, Michał (Kultury Wschodniosłowiańskie – Oblicza i Dialog, 2019)
The article is devoted to the image of war in Smrt – a collection of short stories written by Eduard Limonov. Eduard Limonov is a controversial Russian writer and politician known for his extremist worldview, scandalous literary works and involvement in the national-bolshevik movement. The action of most of the stories is set against the backdrop of the Yugoslav Wars. Limonov describes the dark sides of the war: death, suffering of civilians and atrocities, but at the same time claims that war creates an excellent opportunity to experience a fascinating adventure and to become a true hero. In his opinion, the war is completely consistent with the most basic human instincts, therefore, it is not surprising that many soldiers participate in war with enthusiasm and prefer it to a boring, stabilized life.